Animals in Levothyroxine Model of Thyroid Damage Are Positively Affected by the Consumption of Descurainia sophia L. Extract (Brassicaceae): Descurainia sophia L. Extract Alleviated Thyroid Damage in Animal Model - Farzameh, Fatemeh; Mirzaee, Fatemeh; Talebpour Amiri, Fereshteh; Kashi, Zahra; Shokrzadeh, Mohammad; Azadbakht, Mohammad (Iranian Journal of Pharmaceutical Sciences, 2025)
There are some promising bioactivities related to Brassicaceae plants, including chemoprotective and anti-cancer effects, through various mechanisms which are mainly related to the number of phytochemicals such as glucosinolates and their hydrolysis products, isothiocyanates. The dietary intake of glucosinolate constituents, which are dominant in Brassicaceae plants, has been shown to interfere with the thyroid gland’s iodine uptake and metabolism through competitive inhibition. Descurainia sophia L. (D. sophia) seeds, commonly named Khakshee, possess a great amount of gluconapin, a glucosinolate known for its goitrogenic properties, which potentially may have protective effects on thyroid dysfunctions. The present study evaluated the possible ameliorative activities of hydroalcoholic extract from D. sophia seeds in regulating hyperthyroidism in a levothyroxine-induced rat model. The 70% hot methanol extract from the plant seeds was prepared using the maceration method, and the total glucosinolate content was determined using UV spectrophotometry. The serum thyroid hormone levels and histopathological features of the thyroid gland were assessed to evaluate the protective effects of extract in hyperthyroidism induced by injection of levothyroxine in rats. The administration of the extract by oral route has been associated with a significant decrease in the levels of FT4 and FT3. Further, the treatment group showed a notable reduction in TSH levels. The histopathological findings showed that the consumption of extract attenuated the adverse effects of levothyroxine. Spectrophotometric analysis revealed the presence of glucosinolates in the extract, which was calculated at 24.14 ± 0.8 mmol equivalent of sinigrin per kilogram of dried seeds. Based on the results of this study, it appears that glucosinolates are responsible for protecting D. sophia against levothyroxine-induced thyroid damage in rats. While Brassicaceae plants are recognized for their potential health benefits, particularly in reducing the risk of various diseases, including cancer, limiting the consumption of certain species, such as Khakshee, is important due to the possibility of affecting thyroid hormone levels by these plants.